Plasticity of Mating Duration in Response to Slightly Biased Operational Sex Ratios in the Water Strider (Aquarius remigis): The Effect of Cohabitation Under Standard Laboratory Conditions - Gallup, Andrew C.; Pietruch, Krista; Eldakar, Omar Tonsi (Frontiers in Ecology and Evolution, 2019)
In polygynandrous species, males face the trade-off between the pursuit of increased mating opportunities and securing paternity. Within such systems, males need to accurately assess the social composition of the local environment to maximize fitness. Here, we investigated this capability in the water strider (Aquarius remigis), a semi-aquatic insect known to exhibit a broad spectrum of mating behaviors and inhabit a socially diverse and changing environment. Using a combination of methodological designs to track both within- and between-subject effects, individuals remained in same-sex housing prior to being exposed to slightly biased operational sex ratios (2:1 vs. 1:2) with or without prior cohabitation to determine the effects on mating duration. Results show that males were sensitive to these subtle differences in social conditions, mating for longer periods within male-biased environments, but this was true only under conditions with prior cohabitation. In particular, when individuals could acclimate to the testing environment, mating duration dropped precipitously in female-biased conditions. These findings do not support the view that male water striders have consistent behavioral syndromes, and instead show that individuals are able to differentiate between, and adaptively respond to, small changes in the local sex ratio. In addition to improving our understanding of the plasticity of male mating behavior in this species, this study offers new insights for future laboratory research studying reproductive competition across a diverse range of polygynandrous animals.